Associação do pico de fluxo da tosse e pressões respiratórias máximas no sucesso da extubação: revisão sistemática e metanálise - Sousa, Lílian Rocha de (Universidade Federal de São Carlos, 2024)
Invasive mechanical ventilation (IMV) is crucial for patients with acute respiratory failure, and its prolonged use can lead to complications. The weaning and extubation process should occur as soon as possible, because when there is failure, there is an increase in cost and mortality. Respiratory muscle weakness is associated with prolonged IMV, which makes respiratory muscle strength and cough effectiveness important factors to be considered in extubation. Therefore, it is necessary to investigate the relationship between respiratory muscle strength and cough peak flow measures (CPF) to predict the outcomes of extubation. To conduct a systematic review of the literature, to investigate whether respiratory muscle strength is related to CPF measures, and whether these are predictive together or alone, in the outcome of extubation. The search covered the following databases: PubMed, Web of Science, SciELO and LILACS. The metaphor package was used in the statistical software R Project 3.6.2 to conduct a meta-analysis with fixed and random effects. The variables of interest were analyzed separately, obtaining a forest plot for each variable, where it was possible to observe its influence on the CPF. The residual heterogeneity between the studies was measured by tau² and the proportion of variability was defined by Higgins' I² statistic. The search strategy identified 1167 articles and after the selection of the studies, 3 articles were included in this review. It was observed that the variables age, Maximum Inspiratory Pressure (MIP) and Maximum Expiratory Pressure (MEP) did not significantly influence the CPF of those individuals who were successful in extubation. The variables respiratory muscle strength and CPF were not significantly related to each other, nor together, in the extubation outcome. The CPF, by itself, is able to predict success in extubation. The analyzes indicate the need for more studies to improve the accuracy of the estimates and understand the factors that influence the success of extubation in patients on mechanical ventilation.
Association of peak cough flow and respiratory pressures maxims in extubation success: review systematic and meta-analysis
Keywords: Pico de fluxo expiratório; Tosse; Extubação; Ventilação mecânica; Pressões respiratórias máximas; Desmame; Peak expiratory flow; Cough; Extubation; Mechanical ventilation; Maximum respiratory pressures; Weaning; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL